Association between Cardiac Hypertrophy and Sex of Patients from a Hospital in Ecuador - Guido Nino Guida Acevedo; María Fernanda Cueva Moncayo; Piedad Elizabeth Acurio Padilla (Medisur, 2024)
Foundation: cardiac hypertrophy is macroscopically described as an increase in the thickness of the interventricular wall and/or septum and represents a significant stage prior to heart failure. Many heart conditions tend to show differences between the sexes. Objective: determine the association between cardiac hypertrophy and sex of patients in a hospital of the Ecuadorian Institute of Social Security. Methods: a descriptive and cross-sectional study was carried out in December 2022 in a hospital of the Ecuadorian Social Security Institute. 88 patients were analyzed distributed into two groups: male and female, each with 44 patients. The Mann-Whitney U statistical test was used to determine differences between both groups. Results: patients between 25 and 50 years of age predominated (58.7 %), both males (57.5 %) and females (60 %). In both groups, the majority of patients presented moderate cardiac hypertrophy (52.3 % of both each group and the total). The existence of differences between the degree of cardiac hypertrophy in patients according to their sex could not be demonstrated (result of the Mann-Whitney U test = 934.5; Z = -0.308; p = 0.758). Conclusions: despite the existence of differences in distributions, no relationship was found between sex and the degree of cardiac hypertrophy.